2021
DOI: 10.1155/2021/5512153
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-Mediated m6A RNA Modification Regulates Corneal Injury Repair

Abstract: Limbal stem cells are essential for continuous corneal regeneration and injury repair. METTL3-catalyzed N6-methyladenosine (m6A) mRNA modifications are involved in many biological processes and play a specific role in stem cell regeneration, while the role of m6A modifications in corneal injury repair remains unknown. In this study, we generated a limbal stem cell-specific METTL3 knockout mouse model and studied the role of m6A in repairing corneal injury caused by alkali burn. The results showed that METTL3 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our previous study demonstrated that the epigenetic network is essential for vascular regeneration and functional recovery post-SCI ( Ni et al, 2019 ). The m 6 A methylation plays a significant role in the pathological process of corneal injury, brain injury, and peripheral nerve injury ( Weng et al, 2018 ; Wang et al, 2019 ; Dai et al, 2021 ; Zhang et al, 2021 ). In contrast, various types of cancers and diabetes are associated with lowered m 6 A abundance ( Chen et al, 2020 ; Huang et al, 2021 ; Lei et al, 2021 ; Ruan et al, 2021 ; Wang et al, 2021a ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the epigenetic network is essential for vascular regeneration and functional recovery post-SCI ( Ni et al, 2019 ). The m 6 A methylation plays a significant role in the pathological process of corneal injury, brain injury, and peripheral nerve injury ( Weng et al, 2018 ; Wang et al, 2019 ; Dai et al, 2021 ; Zhang et al, 2021 ). In contrast, various types of cancers and diabetes are associated with lowered m 6 A abundance ( Chen et al, 2020 ; Huang et al, 2021 ; Lei et al, 2021 ; Ruan et al, 2021 ; Wang et al, 2021a ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the involvement of these genes suggests that they may play a role in regulating WNT signaling [ 134 ]. Additionally, knocking out METTL3 in corneal limbal stem cells promotes the proliferation and migration of in vivo cells, resulting in fast repair of corneal injury [ 135 , 136 ]. During corneal injury, CECs also migrate more rapidly.…”
Section: Methylation In Corneal Physiology and Pathologymentioning
confidence: 99%
“…Corneal limbal stem cells possess the ability to regularly renew and differentiate, and they migrate to the central cornea to replace damaged or dead CECs [ 137 ]. This research highlight the crucial role of m 6 A in regulating corneal injury repair and offers new insights for the treatment of CDs [ 136 ].…”
Section: Methylation In Corneal Physiology and Pathologymentioning
confidence: 99%
“…In the acute phase of alkaline injuries, over 50% of corneal limbal ischemia is an influential contributor to the dysfunction of the limbal stem cells [60] . Dai et al [61] created a limbal stem cell-specific METTL3 knockout (cKO) mouse model and investigated the function of m6A in repairing corneal injury after alkali burns. On days 7 and 14 after alkali burns, the METTL3 cKO mice had more complete corneal epithelium and less stromal layer neovascularization compared to wildtype mice, suggesting that METTL3 knockdown inhibited pathological vascularization and promoted corneal injury repair.…”
Section: M6a Modification In Ocular Surface Diseasesmentioning
confidence: 99%